English translation research based on a multimodal corpus of Cantonese opera: a case study of classic Cantonese opera Red Boat - Jiang, Liping (Frontiers in Communication, 2025)
Cantonese Opera, a prominent genre of Chinese traditional opera, showcases the rich heritage and artistic appeal of Chinese culture through its distinct singing style, gestures, costumes, and facial makeup. Despite its cultural significance, Cantonese Opera faces challenges in reaching international audiences due to linguistic and cultural barriers. This paper explores the physical movements and linguistic features of the Cantonese opera Red Boat during its performance, based on a self-built bilingual multimodal corpus of Cantonese opera. It also conducts an analysis of the coordination between the English and Chinese lyrics and recited lines and physical movements. The study reveals that, although the translation retains the catchy nature in terms of tone and rhythm, challenges still exist in the integration of English lyrics with stage actions. When conducting multimodal translation research on Opera, attention should be paid to the coordination between stage action cues and lyrics recited lines in the English translation. This research provides a methodological reference for the multimodal English translation of Cantonese opera and offers new insights for promoting the international dissemination of Chinese Opera.